Structural performance of steel–concrete composite beams with UHPC overlays under hogging moment. (1st November 2022) - Wan, Zhiyong; Fang, Zhi; Liang, Linong; He, Shaohua; Sun, Xiangdong
Highlights: Usefulness of UHPC overlays in improving the performance of composite beams under hogging moment is experimentally evaluated. Impacts of interfacial shear steel rebars and wire meshes on the composite beams is evaluated; Early-age shrinkage effect on cracking performance of the UHPC-NC composite deck is assessed. Analytical model to determine cracking moment for composite beams with UHPC overlay is derived. Abstract: This paper investigates the usage of a thin layer of Ultra-high performance concrete (UHPC) reinforcing the concrete decks at the hogging moment region of steel–concrete composite beam bridges. An integrated experimental and numerical study was conducted to assess the influence of several parameters, such as the type of overlay concrete, arrangement of interfacial shear steel rebars, and presence of wire meshes, on the structural performance of the retrofitted composite beams. In the experimental program, five steel–concrete composite beams, including one normal concrete (NC)-strengthened composite beam and four UHPC-strengthened composite beams, were fabricated and tested. Experimental results indicate that the application of UHPC overlays significantly improved the structural performance of the retrofitted composite beams, and providing wire meshes in UHPC overlays restricted crack propagation of combined UHPC-NC decks. The bending stiffness and cracking resistance of the UHPC-strengthened composite beams were 25.2% and 368.7%, respectively higher than those of the NC-strengthened composite beams. As expected, the shear steel rebars can avoid sliding and uplifting at the substrate-to-overlay interface, and the utilization of shear steel rebars by a ratio of 0.28% magnified the bending stiffness and cracking resistance of the retrofitted beams by 9.7% and 5.1%, respectively, as compared to those without the rebars. In the numerical simulation, a three-dimensional finite element (FE) analysis of the composite beams was carried out, and the simulation results were validated with the experimental data. It is shown that the retrofitted beams under hogging moment finally failed due to fracture of the longitudinal steel reinforcements in the original decks, regardless of the presence of bonded overlays. Moreover, an analytical model for the combined UHPC-NC deck was developed to provide reliable predictions for the composite beams with UHPC overlays under hogging moment.